2020
DOI: 10.1159/000509548
|View full text |Cite
|
Sign up to set email alerts
|

Growth Trajectory and Adult Height in Children with Nonclassical Congenital Adrenal Hyperplasia

Abstract: Background: Children with nonclassical congenital adrenal hyperplasia (NCCAH) often present increased growth velocity secondary to elevation of adrenal androgens that accelerates bone maturation and might compromise adult height (AH). Objective: The aim of the study was to analyze prognostic factors affecting growth trajectory (GT) and AH in children with NCCAH. Methods: The study was a retrospective, multicentric study. The study population consisted of 192 children with a confirmed molecular diagnosis of NCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In contrast, in untreated NCCAH patients, reported final heights are within the normal range in most studies (6,(50)(51)(52), suggesting that the elevated androgens in these patients do not lead to significant growth reduction. However, one study by New et al (53) reported a final height below the target height in untreated NCCAH patients.…”
Section: Growthmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, in untreated NCCAH patients, reported final heights are within the normal range in most studies (6,(50)(51)(52), suggesting that the elevated androgens in these patients do not lead to significant growth reduction. However, one study by New et al (53) reported a final height below the target height in untreated NCCAH patients.…”
Section: Growthmentioning
confidence: 93%
“…There is no clear evidence that final height is significantly decreased in NCCAH patients receiving glucocorticoid treatment during childhood (47,51,66). Wasniewska et al (51) reported no significant difference in final height between treated and untreated patients.…”
Section: Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent European multicenter study looked retrospectively at a group of 192 NC-CAH patients mostly treated with glucocorticoids who achieved adult heights only modestly below the normal range. However, the smaller untreated group (11% of the total) achieved normal and slightly greater adult heights than the treated group ( p = 0.053) [14]. While it is likely that the untreated group had a milder presentation as they were significantly older at diagnosis, it is clear that withholding treatment of NC-CAH does not inevitably lead to rapidly advancing bone age and short stature.…”
Section: Premature Adrenarchementioning
confidence: 99%